The Australian Men's Sheds movement: human resource management in a voluntary organisation. (5th February 2013) - Cavanagh, Jillian; McNeil, Nicola; Bartram, Timothy
<x xml:space="preserve">Abstract</x> This paper examines the Men's Sheds movement – an Australian innovation that is now spreading internationally. This movement has significance for human resource management, both in providing a useful alternative to paid employment for older workers, and as a research site where the human resources challenges peculiar to voluntary organisations can be observed. The paper is underpinned by social exchange theory. The paper's empirical focus is on the factors that govern the level of participation of members in the Men's Sheds movement. The research employs a case study methodology, with focus groups of 34 members in two Australian men's sheds. Predictably, we found that the decision to participate is driven primarily by altruistic motives and reciprocal relationships. However, professional HRM practices remain important. Our findings lend support for the importance of leadership and human resource practices, such as training and development, occupational health and safety, and human resource planning that are used to facilitate effective participation in the sheds.